Restorative policing: concepts, theory and practice - Clamp, Kerry; Paterson, C. (Routledge, 2016)
In the UK and elsewhere, restorative justice and policing are core components of a range of university programmes; however, currently no such text exists on the intersection of these two areas of study. This book draws together these diverse theoretical perspectives to provide an innovative, knowledge-rich text that is essential reading for all those engaged with the evolution and practice of restorative policing.